The perils of populism - Tobias, Sarah, 1963-; Stein, Arlene (The feminist bookshelf : ideas for the 21st century, 2022)
"Contemporary right-wing populist movements have propelled authoritarian leaders into power, championed reactionary forms of nationalism as solutions to economic and social crisis, and scapegoated vulnerable populations, leading to violence, harassment, and hate speech directed against immigrants, people of color, Muslims, Jews, LGBT people and other marginalized communities. The Perils of Populism gathers the writing of leading theorists and activists to explore how a feminist lens can help diagnose the global rise of populism and resist threats to democracy. It reflects on the roots of the current political crisis, shows how feminist and queer activists are challenging reactionary populism, and explores feminist visions of a more just, democratic future. Featuring interdisciplinary essays on the United States, the Middle East, Europe, and India, the volume contributes to a rapidly expanding literature on gender and the far right"--